The influence of green human resource management on employees’ green innovation behavior: The role of green organizational commitment and knowledge sharing - Min Yang; Zhongbin Li (Heliyon, 2023)
Employees' green innovation behavior is a key factor in enterprises' promotion of green development strategies. Combining social information processing and social exchange theory, this article considers workers' green organizational commitment (GOC) as a mediating construct and knowledge sharing as a moderating construct and establishes a model of the influence of green human resource management (GHRM) on workers' green innovation conduct in company settings. An empirical analysis of 436 employees from 28 high-tech enterprises in Fujian Province shows that GHRM has a positive significant bearing on workers' green innovation conduct. Employees' GOC has a positive mediating influence on the interaction between GHRM and employees' green innovation conduct. Employees' knowledge sharing moderates positively the interaction between green organizational commitment and green innovation behavior and moderates the mediating effect of green organizational commitment. Therefore, we propose stimulating employees’ green innovation behavior by implementing green GHRM, focusing on green demand and creating a knowledge-sharing atmosphere.